Andrzej Kijowski o Jarosławie Iwaszkiewiczu - Tomaszewska, Wiesława (Załącznik Kulturoznawczy, 2024)
This article presents the complexity of the relationship between two writers belonging to Polish literature of the twentieth century, Andrzej Kijowski and Jarosław Iwaszkiewicz. Kijowski’s texts, which form the basis of these considerations, concern both Iwaszkiewicz’s artistic work and his personal life, which is revealed through direct interpersonal relations. This distinction corresponds to two groups of Kijowski’s texts about Iwaszkiewicz: (1.) official, i.e. reviews and sketches published in the social and cultural press of the time, and (2.) unofficial, i.e. private diaries, not intended for publication in the author’s intention. Thus, two separate, though complementary literary portraits of Iwaszkiewicz were derived from Kijowski’s writing: an outstanding writer, a great prose writer, who was no stranger to the metaphysical dimension of literature, and an efficient architect of the literary life of the time.